2002
DOI: 10.1073/pnas.102015399
|View full text |Cite
|
Sign up to set email alerts
|

Elevated mutation rates in the germ line of first- and second-generation offspring of irradiated male mice

Abstract: Mutation rates at two expanded simple tandem repeat loci were studied in the germ line of first-and second-generation offspring of inbred male CBA͞H, C57BL͞6, and BALB͞c mice exposed to either high linear energy transfer fission neutrons or low linear energy transfer x-rays. Paternal CBA͞H exposure to either x-rays or fission neutrons resulted in increased mutation rates in the germ line of two subsequent generations. Comparable transgenerational effects were observed also in neutron-irradiated C57BL͞6 and xir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
113
5
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(132 citation statements)
references
References 33 publications
12
113
5
2
Order By: Relevance
“…For both strains, a statistically significant B2-2.8-fold increase in the mean mutation frequency was found in all tissues of the offspring of irradiated males (Table 1). These data therefore confirm our previous results obtained in the germ line of F 1 offspring of irradiated males, using the more traditional pedigree-based approach (Dubrova et al, 2000;Barber et al, 2002) and additionally show that transgenerational genomic instability at ESTR loci is also manifested in somatic tissues. Most importantly, the frequency of ESTR mutation was elevated in the germline (sperm) and somatic tissues of all the offspring of irradiated males (Figure 2a and b).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…For both strains, a statistically significant B2-2.8-fold increase in the mean mutation frequency was found in all tissues of the offspring of irradiated males (Table 1). These data therefore confirm our previous results obtained in the germ line of F 1 offspring of irradiated males, using the more traditional pedigree-based approach (Dubrova et al, 2000;Barber et al, 2002) and additionally show that transgenerational genomic instability at ESTR loci is also manifested in somatic tissues. Most importantly, the frequency of ESTR mutation was elevated in the germline (sperm) and somatic tissues of all the offspring of irradiated males (Figure 2a and b).…”
Section: Resultssupporting
confidence: 91%
“…Our results therefore demonstrate that transgenerational increases in ESTR mutation rates also reflect corresponding changes at protein-coding genes, mutation at which may result in human genetic disorders. Given that in the male offspring of irradiated males the X-linked hprt locus is transmitted from the non-exposed mothers, these data also confirm the previous conclusion that transgenerational changes in mutation rates equally affect both alleles derived from the irradiated fathers and the unexposed mothers, thus implying a genome-wide destabilization after fertilization (Niwa and Kominami, 2001;Barber et al, 2002;Shiraishi et al, 2002;Dubrova, 2003).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, somatic mutation of the Ms6-hm sequence can be induced by radiation in highly proliferating tissues such as spleen, but not in the nonproliferating brain cells (Yauk et al, 2002). In contrast, Dubrova and his group indicated that spermatozoa are again insensitive to radiation induction of minisatellite mutation (Barber et al, 2002). Thus, the discrepancy on the spermatozoa radiosensitivity is not resolved at present.…”
Section: Minisatellite Mutation and Male Spermatogenesismentioning
confidence: 89%